Leveraging social network sites for new product launch - Roberts, Deborah L.; Cani, M.; Hughes, M. (Emerald, 2017)
Purpose – The ability to make use of social network sites (SNSs) to promote new products and facilitate positive word of mouth around new product launch (NPL) presents an important opportunity. However, the mechanisms and motivations of SNS users are not well understood and businesses frequently fail to realize these opportunities. This paper examines some of the forces that motivate people to spend time on SNS sites and how these motivations are related with people’s propensity to engage in behaviours that can be beneficial for NPL.